The Agreement of Immunoglobulin Gamma Release Assay (IGRA)/ T-SPOT Tuberculosis and Tuberculin Skin Test to Detect Latent TB Infection in Diabetes Mellitus Patients - Reviono, Reviono; Sutanto, Yusup Subagio; Harsini, Harsini; Saptawati, Leli; Marwoto, Marwoto; Suryawati, Betty; Redhono, Dhani; Sebayang, Pribadi M (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: WHO identifies diabetes mellitus (DM) as a neglected risk factor for tuberculosis (TB). Currently, there is no gold standard test for latent TB infection (LTBI). Centers for Disease Control and Prevention (CDC) recommends using Tuberculin Skin Test (TST) and Immunoglobulin Gamma Release Assay (IGRA) to diagnose LTBI. TST is an LTBI classic diagnostic tool that has low sensitivity and specificity. But it is still preferred in diagnosing LTBI due to its lower price, and more health facilities can perform the examination compared to IGRA (T-SPOT.TB). The study aimed to measure the agreement of TST and T-SPOT.TB testing in detecting LBTI in DM and the correlation of HbA1c with TST and T-SPOT.TB.Subjects and Method: Subjects were DM patients who underwent TST and T-SPOT.TB testing. If the results of TST and T-SPOT.TB was positive, the test would be continued with Xpert MTB/RIF microbiological testing. TST used PPD RT23 2TU. T-SPOT.TB was performed toward peripheral blood mononuclear cells. The degree of agreement between TST and T-SPOT.TB testing was calculated using the Test of Agreement (Kappa Cohen). The degree of correlation between the two variables was calculated by using Pearson correlation.Results: The selected 30 study subjects with DM undergoing antidiabetic therapy showed 6 (20%) detected LTBI and 24 (80%) without LTBI using TST and T-SPOT.TB test. There was a substantial agreement level between TST and T-SPOT.TB testing in detecting LTBI among diabetes mellitus patients undergoing anti-diabetic therapy with kappa value= 0.62 (p<0.001). HbA1c increased T-SPOT (r= 0.07; p= 0.716) and TST (r= 0.11; p= 0.956).Conclusion: TST testing may substitute T-SPOT.TB to detect LTBI among diabetes patients undergoing antidiabetic therapy.Keywords: latent tuberculosis infection, diabetes mellitus, TST, Immunoglobulin Gamma Release Assay (IGRA), T-SPOT.TBCorrespondence: Reviono. Department of Pulmonology and Medical Respiratory, Faculty of Medicine, Universitas Sebelas Maret/ Dr. Moewardi Hospital, Surakarta, Indonesia. Email: reviono@staff.uns.ac.id.Indonesian Journal of Medicine (2021), 06(03): 298-306https://doi.org/10.26911/theijmed.2021.06.03.07